Effect of Compensation and Motivation for Productivity Work of Employees of Arteria Daya Mulia Cirebon Yarn Production Section - Iqbal, Fariz; Kartono, Kartono; Puji Astuti, Ramlah (Jurnal Ekuisci, 2024)
This study discusses the influence of compensation and motivation on employee work productivity at PT. Arteria Daya Mulia. The research aims to identify the factors influencing the performance of employees in the yarn production department. A survey method with a simple random sampling technique was employed in this study. The results indicate that compensation and motivation have a positive impact on employee work productivity. Therefore, the company needs to enhance employee compensation and motivation to improve work productivity. This research can be applied to other industries beyond PT. Arteria Daya Mulia.